Mengenalkan Keterampilan dan Pendidikan yang Dibutuhkan pada Era New Digital Economy Melalui Program Kampus Merdeka - Ika Sari Tondang; Keriapy, Donny (Abdi Psikonomi, 2022)
Abstract The Merdeka Campus is part of the Freedom to Learn policy by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia which provides opportunities for students to hone their abilities according to their talents and interests by going directly into the world of work as preparation for future careers. RevoU is an online learning academy created to develop careers and equip students with the skills and education needed in the new digital economy era and focuses on training students who wish to develop their careers in the technology industry and connecting them with instructors from leading technology companies in Southeast Asia. Through Merdeka Learn Kampus Merdeka (MBKM), RevoU participates in the 3rd year 2022 Certified Internship & Independent Study (MSIB) program by developing a program called RevoU Tech Academy. RevoU Tech Academy is a program aimed at all students with various educational backgrounds to study four important areas in the technology industry, namely digital marketing, tech sales, data analytics, and product management. This program lasts for six months from 16 August 2022 to 23 December 2022. At the end of the lesson there is a capstone project, the final project of the program to complete a direct project with a specified theme. Keywords: Digital marketing, data analytics, tech sales, product management, revou, independent study, independent campus, independent learning